A new barbiturate-based centrosymmetric compound: Joint experimental/DM investigation of the structural, spectroscopic and surface properties - Sen, Fatih; Capan, Irfan; Dincer, Muharrem; Cukurovali, Alaaddin (Elsevier, 2018)
A combined experimental and OFT studies on molecular structure along with spectral investigation on the title compound which is a barbiturate derivative with the formula [C34H40N2O5], 5,5-diethy1-1,3-Bis(2-(3-methy1-3-phenylcyclobuty1)-2-oxoethyppyrimidine-2,4,6(1H,3H,5H)-trione, has been reported. The crystal and molecular structures of compound were uncovered by single -crystal X-ray diffraction (SCXRD) technique. The starting geometry was obtained from the X-ray structure determination was optimized using density functional theory (DFT/B3LYP) method with the 6-31G(d) and 6-31 G(d, p) basis sets in ground state. From the optimized geometry of the molecule, geometric parameters (bond lengths and bond angles), vibrational assignments and chemical shifts of the title compound have been calculated theoretically and compared with the experimental data(SCXRD, FT-IR and NMR). Molecular Electrostatic Potential (MEP) map and Hirshfeld surfaces of the compound are obtained by using the optimized structures and Crystal Explorer software, respectively. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Barbiturate; Cyclobutane; X-Ray diffraction; IR and NMR; DFT; Hirshfeld surface